1984
DOI: 10.4141/cjss84-036
|View full text |Cite
|
Sign up to set email alerts
|

CHANGES IN NATURAL 15N ABUNDANCE OF SOILS ASSOCIATED WITH TILLAGE PRACTICES

Abstract: The objective of this study was to determine changes in N dynamics in an Orthic Black Chernozem as a result of two tillage practices (conventional and zero tillage) using the variations in the natural 15N abundance of different soil-N fractions. After 14 yr, no significant differences in isotope composition of total soil-N between the two tillage practices could be found. However, changes were detected in the natural 15N abundance of the acid-hydrolyzable N and various organo-mineral size fractions which led t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0

Year Published

1993
1993
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 5 publications
2
11
0
Order By: Relevance
“…The C : N ratios generally decreased from coarse to fine fractions, thereby indicating the tendency of fine fractions to be relatively more important as N sink than as organic-C sink. These results are in agreement with previous studies where decreasing C : N ratios with smaller particle sizes were observed (Selles et al, 1984;Stemmer et al, 1988;Kandeler et al, 1999;Gerzabek et al, 2001b). Gener-…”
Section: Nitrogen and C : N Ratios In Particle-size Fractionssupporting
confidence: 83%
See 1 more Smart Citation
“…The C : N ratios generally decreased from coarse to fine fractions, thereby indicating the tendency of fine fractions to be relatively more important as N sink than as organic-C sink. These results are in agreement with previous studies where decreasing C : N ratios with smaller particle sizes were observed (Selles et al, 1984;Stemmer et al, 1988;Kandeler et al, 1999;Gerzabek et al, 2001b). Gener-…”
Section: Nitrogen and C : N Ratios In Particle-size Fractionssupporting
confidence: 83%
“…Comparing N contents in particle-size fractions with the N content in bulk soil by calculating their ratios (N concentration in the respective fraction divided by N concentration in bulk soil; data not shown), we observed on average enrichment in fine fractions (silt: 1.36; clay: 2.14) and depletion in coarse fractions (coarse sand: 0.20, fine sand: 0.53). Several authors have confirmed that N contents increase with decreasing particle size (e.g., Gerzabek et al 2001b;Selles et al, 1984;Stemmer et al, 1998). Schulten (1998, 2000) gave evidence for several longterm (5±108 yr) studies in Germany that this pattern is influenced by the adsorption of organic N on reactive surfaces of soil compounds (silicates, pedogenic oxides, alkali-extractable organic substances).…”
Section: Nitrogen and C : N Ratios In Particle-size Fractionsmentioning
confidence: 92%
“…Selles et al (1984) tested this premise directly and found no significant change in soil δ 15 N at any depth due to tillage (Figure 7C). It is therefore unlikely that soil tillage is a significant contributor to variation in ancient plant N isotopic compositions.…”
Section: Agricultural Practicesmentioning
confidence: 95%
“…Reduced tillage concentrates crop residues, organisms and organic matter (Selles et al 1984;Doran et al 1987), increases immobilization of fertilizer N, and decreases carbon and net N mineralization over time in the 0-to 5-cm layer of soil (Doran 1980;Linn and Doran 1984;Coleman 1985). In the shortrun, the mineralization-immobilization turnover (MIT) of N slows under ZT and organic matter accumulates (Fredrickson et al 1982: House et al 1984Rice and Smith 1984; Carter and Rennie 1987: Doran et al 1987).…”
mentioning
confidence: 99%